Unveiling metabolic pathways of selected plant-derived glycans by Bifidobacterium pseudocatenulatum - Sanchez-Gallardo, Rocio; Bottacini, Francesca; Friess, Lisa; Esteban-Torres, Maria; Somers, Clarissa; Moore, Rebecca L.; McAuliffe, Fionnuala M.; Cotter, Paul D.; van Sinderen, Douwe (Frontiers in Microbiology, 2024)
Bifidobacteria are commonly encountered members of the human gut microbiota that possess the enzymatic machinery necessary for the metabolism of certain plant-derived, complex carbohydrates. In the current study we describe differential growth profiles elicited by a panel of twenty-one newly isolated Bifidobacterium pseudocatenulatum strains on various plant-derived glycans. Using a combination of gene-trait matching and comparative genome analysis, we identified two distinct xylanases responsible for the degradation of xylan. Furthermore, three distinct extracellular α-amylases were shown to be involved in starch degradation by certain strains of B. pseudocatenulatum. Biochemical characterisation showed that all three α-amylases can cleave the related substrates amylose, amylopectin, maltodextrin, glycogen and starch. The genes encoding these enzymes are variably found in the species B. pseudocatenulatum, therefore constituting a strain-specific adaptation to the gut environment as these glycans constitute common plant-derived carbohydrates present in the human diet. Overall, our study provides insights into the metabolism of these common dietary carbohydrates by a human-derived bifidobacterial species.